(untitled) (ARQUISUR Revista, 2022)
The dominant consumption of non-renewable energy associated with urban growth directly affects the world’s environmental resources. Within this framework, the energy policies of many countries promote the distributed generation of photovoltaic solar energy stands out. However, for its territorial deployment, it is necessary, among other things, to have project guidelines for urban land occupation based on the integration of these technologies in the built habitat. Accordingly, the aim of this work is to design it by selecting a case study and defining a project in accordance with the urban-architectural possibilities. It is concluded that this proposal represents a contribution to sustainable urban spatial and architectural design.